Hydrodynamic stability of tension leg platform (TLP) - Mohd Hafiz bin Naib Muddin, Mohd Hafiz (2009)
This report basically describes the hydrodynamic stability of Tension Leg Platform (TLP) due to wave and current. First part of this report. it gives information on Background Studies and the objective of the research. Literature Review is the second part of this report and it describes on types of TLP, buoyancy and stability of TLP the scale modeling of a prototype.